Author Correction: Evaluating Tumor Evolution via Genomic Profiling of Individual Tumor Spheroids in a Malignant Ascites. Issue 1 (December 2018) - Kim, Sungsik; Kim, Soochi; Kim, Jinhyun; Kim, Boyun; Kim, Se; Kim, Min; Kwon, Sunghoon; Song, Yong
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.